2012
DOI: 10.1089/thy.2011.0311
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Distribution of the Sodium Iodide Symporter in Benign and Malignant Thyroid Tissues

Abstract: Confocal staining strictly evaluating only membranous expression of NIS has not used on a large scale before this study. We confirm the loss of membranous NIS in benign but more prominently in malignant thyroid tumors. NIS staining of diagnostic tissues cannot be used to predict RIU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Such differences may be due to the variable size of the series and to differences in the antibodies used to perform the IHC (almost every study uses its own antibody, Table 4 ). In fact, one study compared NIS immunostaining using two different antibodies in a large series of thyroid carcinomas and observed some differences in the percentage of positive cells ( 29 ). To be sure that we were not missing any signal, we performed the IHC for NIS with TSA signal amplification in a subset of carcinomas with different immunostaining patterns and observed a complete vanish of intracytoplasmic staining and an amplification of the membrane staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such differences may be due to the variable size of the series and to differences in the antibodies used to perform the IHC (almost every study uses its own antibody, Table 4 ). In fact, one study compared NIS immunostaining using two different antibodies in a large series of thyroid carcinomas and observed some differences in the percentage of positive cells ( 29 ). To be sure that we were not missing any signal, we performed the IHC for NIS with TSA signal amplification in a subset of carcinomas with different immunostaining patterns and observed a complete vanish of intracytoplasmic staining and an amplification of the membrane staining.…”
Section: Discussionmentioning
confidence: 99%
“…Although positive NIS immunostaining in primary tumors seemed to be predictive of positive recurrences and metastases on 131 I scans, other studies did not distinguish whether NIS was expressed in the cell basolateral membrane, and negative NIS staining did not predict 131 I scan-negative metastases ( 13 , 15 , 18 ). Even when only NIS membrane staining was considered, a negative NIS staining in the primary tumor was still not predictive of a negative 131 scan of subsequent recurrences ( 29 ). To the best of our knowledge, there is only one study that addressed possible associations between NIS expression, evaluated by immunohistochemistry (IHC), and clinicopathological features and prognosis in a large series of thyroid primary tumors ( 1 ), reporting a significantly lower NIS expression in older patients (≥45 years) and also that NIS expression in the primary tumor was not useful as a prognostic marker.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for radioactive‐iodine remnant ablation failure is lower sodium‐iodide symporter (NIS) expression in patients with coexisting Hashimoto thyroiditis, which was associated with decreased radioactive iodine uptake into the remnant thyroid tissue . Thyroid tissue with Hashimoto thyroiditis showed significantly lower levels of NIS membrane staining than normal thyroid tissue . Inflammatory changes of thyroid tissue may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…22 Thyroid tissue with Hashimoto thyroiditis showed significantly lower levels of NIS membrane staining than normal thyroid tissue. 23 Inflammatory changes of thyroid tissue may also play a role. In a recent clinical study, high dose (3700 MBq) radioactive-iodine remnant ablation demonstrated a lower success rate of 33.4% in patients with thyroiditis, whereas patients without thyroiditis had a success rate of 80%.…”
Section: Discussionmentioning
confidence: 99%
“…express high levels of NIS compared with their normal counterparts; however, this expression decreases to undetectable levels when the cancer becomes undifferentiated (16,(31)(32)(33)(34). Our data show that iodine supplementation for 24 wks does not modify the basal expression of NIS in normal prostate, but it prevents the overexpression in cancerous prostate.…”
Section: Discussionmentioning
confidence: 63%